THE EVOLUTION OF PROFESSIONAL ROLES IN THE AGE OF GENERATIVE AI - Камишева, М. (SWorldJournal, 2025)
The article on the study of the evolution of professional roles in the era of generative artificial intelligence is devoted to the analysis of artificial intelligence tools and their impact on various aspects of professional activity in the conditions of